Exosomes Derived from Schistosoma japonicum Cystatin-Treated Macrophages Attenuated CLP-Induced Sepsis in Mice - Feifei Huang; Yayun Qian; Huihui Li; Liang Chu; Chen Wan; Qili Shen; Qianqian Li; Xiuxiu Li; Xinyue Wu; Bin Zhan; Rui Zhou; Xiaodi Yang (Journal of Immunology Research)
Sepsis is a disease caused by multiple microbial infections resulting in multiple organ failure. Schistosoma japonicum secreted cystatin (Sj-Cys) is a strong immunomodulator that stimulates M2 macrophages and alleviates inflammatory damage caused by sepsis. To determine whether the therapeutic effect of Sj-Cys on sepsis can be conveyed by the exosomes released by Sj-Cys-stimulated macrophages, RAW264.7 macrophages were stimulated with rSj-Cys in vitro, the exosomes were obtained from the cell culture supernatant by ultracentrifugation. Sepsis was induced in BALB/c mice by cecal ligation and puncture (CLP). The septic mice were treated with exosomes derived from Sj-Cys-treated macrophages. The treatment effect of exosomes on sepsis was assessed by examining the survival rate of mice up to 72 hr and measuring serum levels of inflammatory cytokines, liver/kidney damage biomarkers, and observing pathological changes in tissue sections. The tissue levels of M1, M2 macrophage surface markers, and TRL2/MyD88 were measured to explore possible mechanisms. Results. Exosomes derived from Sj-Cys-treated macrophages exhibited significant therapeutic effect on CLP-induced sepsis in mice with prolonged survival rate and less damage of critical organs by downregulating the proinflammatory factors TNF-α and IL-6 and upregulating the anti-inflammatory factor TGF-β. The therapeutic effect of exosomes is associated with macrophage polarization from M1 to M2 in the infected tissues via downregulating TRL2/MyD88 inflammatory pathway. Conclusions. Exosomes derived from Sj-Cys-treated macrophages attenuated sepsis in mice through promoting macrophage polarization from M1 to M2 and reducing inflammatory responses, possibly via downregulating TLR2/MyD88 inflammatory signaling pathway. This offers new approaches for immunotherapy of sepsis.